Perancangan Model Data Flow Diagram Untuk Mengukur Kualitas Website Menggunakan Webqual 4.0 - Hapsari, Karina; Priyadi, Yudi (JSINBIS (Jurnal Sistem Informasi Bisnis), 2017)
The more competition the e-commerce company and the development of technology company in Indonesia, website of Zalora Indonesia traffic rank declining. Measuring the quality of website by using WebQual 4.0 will help manage the web to be able to adjust the quality of the web with user perception. Â The research aims to make design of Data Flow Diagram model to measure website quality using WebQual 4.0 based on user satisfaction variable. A case study was conducted on the Zalora Indonesia website. Data Flow model is used to make design of system model recommendation, while WebQual 4.0 method is used to measure website quality to user satisfaction. The research data using primary data in the form of questionnaires involving 384 respondents in the city of Bandung who had transacted on the website Zalora Indonesia. Data analysis technique applies descriptive analysis. Based on the research result on the quality of the website Zalora Indonesia, simultaneous positive and significant impact on user satisfaction Zalora Indonesia website. t test result showed that three variables partially have a posotive impact on user satisfaction Zalora Indonesia website is usability quality, information quality and service interaction quality, with Information quality variable has largest impact. Therefore, the modeling system using the Context Diagram-Data Flow Diagram focused on information quality variable.Â